Role of platelet membrane glycoprotein IIb-IIIa in agonist-induced tyrosine phosphorylation of platelet proteins (The Rockefeller University Press, 1990)
Treatment of platelets with thrombin was shown previously to induce rapid changes in tyrosine phosphorylation of several platelet proteins. In this report, we demonstrate that a variety of agonists which induce platelet aggregation also stimulate tyrosine phosphorylation of three proteins with apparent molecular masses of 84, 95, and 97 kD. Since platelet aggregation requires the agonist-induced activation of an integrin receptor (GP IIb-IIIa) as well as the binding of fibrinogen to this receptor, we examined the relationship between tyrosine phosphorylation and the function of GP IIb-IIIa. When platelets were examined under conditions that either precluded the activation of GP IIb-IIIa (prior disruption of the complex by EGTA at 37 degrees C) or the binding of fibrinogen (addition of RGDS or an inhibitory mAb), tyrosine phosphorylation of the 84-, 95-, and 97-kD proteins was not observed. However, although both GP IIb-IIIa activation and fibrinogen binding were necessary for tyrosine phosphorylation, they were not sufficient since phosphorylation was observed only under conditions in which the activated platelets were stirred and allowed to aggregate. In contrast, tyrosine phosphorylation was not dependent on another major platelet response, dense granule secretion. Furthermore, granule secretion did not require tyrosine phosphorylation of this set of proteins. These experiments demonstrate that agonist-induced tyrosine phosphorylation is linked to the process of GP IIb-IIIa-mediated platelet aggregation. Thus, tyrosine phosphorylation may be required for events associated with platelet aggregation or for events that follow aggregation.